Survey of Interests of Middle School Students in Karang Tinggi, Bengkulu Tengah on Online Sports Learning during the Covid-19 Pandemic - Citra Dewi; Desrio Windoro; Rio Hardiansyah (Perkumpulan Dosen Muda Bengkulu, 2021)
The world is currently experiencing an outbreak of a coronavirus that can cause a disease called COVID-19. COVID-19 that occurred in various countries including Indonesia has an impact on various fields including education. Currently the world of education is facing quite complex problems. The virus attack has an impact on the implementation of learning at all levels of education. This study aims to determine and analyze the survey of student interest in PJOK learning during the COVID-19 pandemic in junior high schools in Karang Tinggi District, Central Bengkulu, Bengkulu Province. The research method used is quantitative method. This method is a research method used to examine the population and sample. Data analysis is quantitative statistic with the aim of testing the hypothesis that has been applied and this research method uses a survey method. while the data collection using a questionnaire. Sampling technique is a sampling technique. Sampling techniques are basically grouped into two, namely probability sampling and non-probability sampling as many as 30 people. From the description of the research results, it can be seen that the interest of junior high school students in the Karang Tinggi sub-district based on physical indicators in participating in online sports learning during the Covid-19 pandemic was the most in the medium category 56.7%. Very high category 18.7%, High 13.3%, Low 10%, very low 3.3%. Activity indicators in the high category are 46.7%. Very high category 3.3%, Medium 26.7%, Low 16.7%, very low 6.7%. Meanwhile, the indicator of feeling in the moderate category is 70%. Very high category 3.3%, High 10%, Low 10%, very low 6.7%.